Phenotypic and Methylome Responses to Salt Stress in Arabidopsis thaliana Natural Accessions - Lin, Xiaohe; Zhou, Ming; Yao, Jing; Li, Qingshun Q.; Zhang, Yuan-Ye (Frontiers in Plant Science, 2022)
Salt stress threatens plant growth, development and crop yields, and has become a critical global environmental issue. Increasing evidence has suggested that the epigenetic mechanism such as DNA methylation can mediate plant response to salt stress through transcriptional regulation and transposable element (TE) silencing. However, studies exploring genome-wide methylation dynamics under salt stress remain limited, in particular, for studies on multiple genotypes. Here, we adopted four natural accessions of the model species Arabidopsis thaliana and investigated the phenotypic and genome-wide methylation responses to salt stress through whole-genome bisulfite sequencing (WGBS). We found that salt stress significantly changed plant phenotypes, including plant height, rosette diameter, fruit number, and aboveground biomass, and the change in biomass tended to depend on accessions. Methylation analysis revealed that genome-wide methylation patterns depended primarily on accessions, and salt stress caused significant methylation changes in ~ 0.1% cytosines over the genomes. 33.5% of these salt-induced differential methylated cytosines (DMCs) were located to TEs. These salt-induced DMCs were mainly hypermethylated and accession-specific. TEs annotated to have DMCs (DMC-TEs) across accessions were found mostly belonged to the superfamily of Gypsy, a type II transposon, indicating a convergent DMC dynamic on TEs across different genetic backgrounds. Moreover, 8.0% of salt-induced DMCs were located in gene bodies and their proximal regulatory regions. These DMCs were also accession-specific, and genes annotated to have DMCs (DMC-genes) appeared to be more accession-specific than DMC-TEs. Intriguingly, both accession-specific DMC-genes and DMC-genes shared by multiple accessions were enriched in similar functions, including methylation, gene silencing, chemical homeostasis, polysaccharide catabolic process, and pathways relating to shifts between vegetative growth and reproduction. These results indicate that, across different genetic backgrounds, methylation changes may have convergent functions in post-transcriptional, physiological, and phenotypic modulation under salt stress. These convergent methylation dynamics across accession may be autonomous from genetic variation or due to convergent genetic changes, which requires further exploration. Our study provides a more comprehensive picture of genome-wide methylation dynamics under salt stress, and highlights the importance of exploring stress response mechanisms from diverse genetic backgrounds.